The Impact of Inventory Turnover and Receivable Turnover Towards ROA (Case Study on Cosmetics and Households Good Company Listed on the Indonesia Stock Exchange in the Period of 2011 - 2017) - Assyifa Hesaputri Suryawan (AIBPM Publisher, 2021)
This study aims to analyze the effect of inventory turnover and receivables turnover on ROA partially on cosmetics and household industry company listed in Indonesia Stock Exchange in the period 2011 - 2017. The research method used is descriptive and verification method with the unit of analysis examined by the financial statements of cosmetic and household industry company listed in Indonesia Stock Exchange. Sampling technique used is purposive sampling where the company need to pass the criteria, companies of cosmetics and household goods industry companies registered with IDX for the period 2011 – 2017, Publish financial statements which had been audited without ever being absent from 2011 – 2017, and financial reports data is in Rupiah. This research uses classic assumption test to have a good regression model consist of normality, multicollinearity, autocorrelation, heteroskedasticity test. Multiple linear regression analysis, Pearson coefficient of correlation, and R square analysis. The result showed that inventory turnover and receivable turnover has a positive effect on ROA partially in cosmetic and household industry company listed in Indonesia Stock Exchange in the period 2011 - 2017. The findings of this study suggest that the companies should maintain their inventory turnover and receivables turnover to have a good ROA.